Konsep Matematika dalam Hadis Zakat Maal: Peluang Integrasi Sains dan Nilai Islam - Sa'adah, Zumrotus (Es-Syajar:Journal of Islam, Science and Technology Integration, 2025)
The purpose of this study is to explore the mathematical concepts contained in the hadiths on livestock and agricultural zakat maal. The lack of studies that explicitly reveal the mathematical content in the hadith text, especially related to zakat maal, provides an opportunity to conduct normative studies on the hadiths that contain detailed provisions related to nishab, zakat levels, and property classification, which indirectly reflect a strong logical and numerical structure. This study uses a literature study method (library research) with a qualitative descriptive approach. Data were obtained from authentic hadith books, such as Sahih Bukhari, Sahih Muslim, and Sunan Abu Dawud, as well as relevant fiqh references and scientific articles. The data analysis technique was carried out through a content analysis approach to identify and describe the mathematical content in the hadith. The results of the study indicate that the hadiths on zakat maal contain various mathematical concepts, including: (1) linear inequalities in zakat on camels and agricultural products; (2) bijective functions and arithmetic sequences in determining camel zakat; (3) data grouping and implication logic in goat zakat; (4) comparison, multiples, and arithmetic operations in cow zakat; and (5) the concept of fractional numbers, multiplication of fractions, and conversion to percentages in agricultural zakat. These findings indicate that hadith not only functions as a source of sharia law, but can also be used as an authentic context for learning mathematics.